LTE Location Technologies and Delivery Solutions. (28th August 2013) - Cherian, Suma S.; Rudrapatna, Ashok N.; Urie, Alistair; Valenzuela, Reinaldo
Abstract With the rapid growth of mobile communication systems, user location is proving to be an important asset for end users, operators, application service providers, enterprises, public safety and law enforcement officials, and others. There are a vast number of applications and use cases that exploit location capabilities, each with a diverse set of needs and requirements in terms of accuracy, latency, and scalability. Long Term Evolution (LTE) technology offers multiple methods for determining and delivering location information. The method chosen must meet and be tailored to the needs of the application and use case for which it is being designed. In this paper, we will discuss location determination and delivery methods in LTE, realizable and simple network architectures necessary to support them, and offer a comparative analysis and recommendations. We will also address representative use cases, their requirements, and solutions. © 2013 Alcatel‐Lucent.